EVALUASI SISTEM PEMBELIAN SPAREPART ( STUDI KASUS PADA PT. KALIMANTAN PRIMA PERSADA TAHUN 2011) - Aswan, Suasti; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2013)
PT. Kalimantan Prima Persada Site Rantau is one of the coal mines in South Kalimantan, precisely in the village Sabah district Rantau. The Company has various Divisions, on of that is a Inventory division (Inventory) which is at the Logistic. Inventory in the company’s goal is to minimize the breakdown unit (stop or can not operate anymore) and to minimize the funds of the company.This study aims to determine the deviations in the sparepart inventory purchase, transaction procedure and to determine the effectiveness of internal control system of the purchase system in PT. Kalimantan Prima Persada. The form of testing used in this study is testing the internal control system of internal control of spareparts inventory purchases PT. Kalimantan Prima Persada in 2011 by using the method of attributte sampling. Which is the method of quantitative tools Fixed Sample Size Attributte Sampling. The types of data collected in this study is documentary data. Purchase data as the main document and permit and also the supporting document such as Recommended Order and Purchase Ordet data.This study has shown that the activity of the Internal Control Structure Inventory Purchases Sparepart PT. Kalimantan Prima Persada whole has gone well and effectively (AUPL < DUPL, AUPL =3 %, DUPL =5%).